246 IMPROVED GROWTH AND DECREASED MORBIDITY IN EXTREMELY LOW BIRTH WEIGHT INFANTS WITH EARLY CONTINUOUS POSITIVE AIRWAY PRESSURE AND AGGRESSIVE NUTRITION. Issue 1 (1st January 2007) - Fonseca, R.; Caskey, M.; Malloy, M.; Geary, C.
Abstract : Purpose: To investigate the clinical impact of three benchmark clinical changes in our neonatal intensive care unit introduced in the fall of 2003. Clinical changes included (1) continuous positive airway pressure (CPAP) after a dose of surfactant at delivery, (2) lower targeted oxygen saturations, and (3) early total parenteral nutrition. Methods: We performed a retrospective cohort study of all premature infants with birth weight less than 1, 000 g, appropriate for gestational age, without congenital anomalies, and born in the specified time period. Group I, n = 87, between January 1, 2001, and June 30, 2002, and between July 1, 2004, and December 31, 2005, group II, n = 78. Results: Infants in group II averaged 17 fewer days on mechanical ventilation, 15% decrease in BPD, 70% decrease in severe BPD, 70% decrease in home oxygen, 50% decrease in pressor use in the first 24 hours of life, 67% decrease in steroid use, 15 fewer central line days, increased rate of weight gain, 10 day decrease in length of stay, and 47% decrease in inguinal hernia repairs. No changes were seen in the incidences of intraventricular hemorrhage, periventricular leukomalacia, pulmonary hemorrhage, pneumothorax, spontaneous intestinal perforations, or necrotizing enterocolitis, although this study was not adequately powered to test these morbidities. Combining cohorts, of all infants who developed BPD, 74% were exposed to mechanical ventilation in their first 48 hours of life. Conclusions: Physiologically appropriate changes in the nutritional and respiratory management of the extremely low birth weight neonate are associated with improvement in multiple morbidity and growth outcomes. Decreased exposure to barotrauma, decreased oxygen toxicity, and more aggressive parenteral nutrition are associated with a reduction in morbidities associated with poor neurodevelopmental outcomes for high-risk neonates. In addition, successful management on CPAP for the first 48 hours after dosing with surfactant of life appears to be protective against the development of BPD.